Delayed Diagnosis of Tuberculous Arthritis of the Knee in an Air Force Service Member: Case Report and Review of the Literature. Issue 3 (1st March 2016) - Triplett, Drew; Stewart, Elizabeth; Mathew, Stephanie; Horne, Brandon R.; Prakash, Vidhya
ABSTRACT: Tuberculosis (TB) is a common disease worldwide affecting more than 2 billion people, including latent, pulmonary, and extrapulmonary TB. The presentation of disseminated TB is variable and dependent on the organs affected. Therefore, making the diagnosis and providing appropriate treatment can be delayed. We present a case of disseminated TB in a patient with Sjögren's syndrome on hydroxychloroquine monotherapy without traditional risk factors.